Facies, Geochemistry, and Ceramic Properties of Corumbataí Formation, Upper Permian of Paraná Basin, and its Application in the Ceramic Industry, Brazil - Christofoletti, Sergio Ricardo; Batezelli, Alessandro; Moreno, Maria Margarita Torres (My University, 2022)
The supply of Corumbataí Formation rocks, which occur widely in the State of São Paulo, Brazil, and are used by Santa Gertrudes Ceramic Cluster, is dwindling and prospecting for new deposits is essential. The current study aimed to map and characterize new reserves of ceramic raw materials which would guarantee mineral and economic sustainability of the important concentration of ceramic-processing capability in that area, and thereby contribute to improving and diversifying the range of products manufactured and to promoting a greater presence in the international market. To achieve the proposed objectives, 16 profiles were sampled and the samples were submitted to granulometric analysis by laser diffraction, and the major elements by inductively coupled plasma-mass spectrometry, and the mineralogical compositions of clay samples were determined by X-ray diffraction and ceramic properties. Six lithofacies were identified and grouped into two facies associations: a lower shoreface association comprising massive siltstone (Sm) and laminated siltstone (Sl); lithofacies, and an upper shoreface association comprising heterolithic sandstone (Sh), lenticular sandstone (Sle), intercalated sandstone/siltstone (Si), and altered siltstone (Sa) lithofacies. The lithofacies of the lower shoreface association were more clayey, flux with a significant presence of illite and microcline, and a more uniform granulometry distribution, which made its classification possible, technologically, as stoneware and semi stoneware. The main application of this material is in the production of coatings through the wet milling process. The lithofacies of the upper shoreface association was sandier, had a refractory presence with kaolinite and montmorillonite, and had a less uniform granulometric distribution; technologically, it can be characterized as porous and semi-porous. The main application of this material is in the production of coatings by the dry milling process. The results obtained by facies analysis combined with the geochemical and ceramic properties of the Corumbataí Formation rocks revealed both vertical and lateral variations of the lithofacies, which influence their properties, behavior, and application as ceramic raw materials.
Keywords: Ceramic raw materials; Clay; Corumbataí Formation; Lithofacies